answersLogoWhite

0


Best Answer

-2

User Avatar

Wiki User

13y ago

Still curious? Ask our experts.

Chat with our AI personalities

FranFran
I've made my fair share of mistakes, and if I can help you avoid a few, I'd sure like to try.
Chat with Fran
ViviVivi
Your ride-or-die bestie who's seen you through every high and low.
Chat with Vivi
DevinDevin
I've poured enough drinks to know that people don't always want advice—they just want to talk.
Chat with Devin

Add your answer:

Earn +20 pts
Q: What is 6 x -2 over 6?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

6 over x plus x over 2 equals 4?

6, 2


How so solve x over 6 equals 18 over 9?

18 over 9 = 2 so x over 6 = 2 making x = 6 x 2 ie 12


What is 1 over 3 by 2 over 2 by 3 over 6?

(1/3) x (2/2) x (3/6) = 1/6


How do you solve x over 2 minus x over 6 equals 1?

x/2 - x/6 = 1 Multiply each term by 6: 3x - x = 6 that is 2x = 6 so that x = 3


If 4 plus x over 6 equals 6 what would x equals?

x=12 because 12 over 6 is 2,and 2 plus 4 is 6.


X over 2 plus 1 over 3?

x/2 + 1/3 = (x/2)(3/3) + (1/3)(2/2) = 3x/6 + 2/6 = (3x + 2)/6


Solve the proportion 2 over 6 equals x over 30?

2/6=x/30 60=6x 10=x


What is the least common denominator for 1 over 6 and 1 over 8?

6 = 2 x 3 8 = 2 x 2 x 2 LCM = 2 x 2 x 2 x 3 = 24


Is 2 and 3 over equivalent to 2.6?

You didn't say what it was over; so the answer is no unless it is over x, where 2 + 3/x = 2.6 Solve for x. 3/x = 2.6 - 2= 0.6 = 6/10 x/3 = 10/6 x = 30/6 = 5


What is 4 over 6 equal x over 3?

x=2


What is the answer for x plus 10 over 2 equals x-6 over x And need to cross multiply?

(x + 10)/2 = (x - 6)/x. Multiply both sides by 2x to produce: x2 + 10x = 2x - 12 Rearrange and collect like terms to produce: x2 + 8x + 12 = 0 Factoring produces: (x + 6)(x + 2) = 0, which is true whenever x = -6 or x = -2 Check: for x - -6: (-6 + 10)/2 = 2; (-6 - 6)/-6 = -12/-6 = 2 (-2 + 10)2 = 4; (-2 - 6)/-2 = -8/-2 = 4.


What is the answer to 2 over x plus 1 over 3 equals 4 over x?

If 2/x + 1/3 = 4/x,multiply each term by 3x, then 6 + x = 12.Subtracting 6 from each side, x = 6.Verifying left side by substituting 6 for x, 2/6 + 1/3 = 1/3 + 1/3 = 2/3;verifying right side by substituting 6 for x, 4/6 = 2/3.